Pourquoi ne pas en finir avec la tarification progressive de l'eau à Bruxelles ? - Xavier May; Pauline Bacquaert; Jean-Michel Decroly; Léa de Guiran; Chloé Deligne; Pierre Lannoy; Valentina Marziali (Brussels Studies, 2021)
In 2005, the Brussels-Capital Region switched from linear pricing to progressive pricing per person because the latter was supposed to be social and ecological. We show that poor households do not consume less water per person than rich households in Belgium and Brussels. Tiered pricing therefore does not benefit poor households and is not social. We also point out that there is no evidence that progressive pricing has encouraged Brussels residents to reduce their already low water consumption. It would therefore not be environmentally friendly either. On the other hand, progressive pricing has a number of disadvantages and leads to serious problems of equity. We therefore advocate a return to linear water pricing for all in Brussels.